1983
DOI: 10.1071/wr9830259
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Melomys burtoni, the Grasslnad Melomys (Rodentia : Muridae) at Cobourg Peninsula, N.T

Abstract: Reproduction, population dynamics, movements, and habitat preferences of Melomys burtoni were studied through a capture-mark-release program on Cobourg Peninsula. In 8714 trap-nights; 143 individuals were captured over 116 weeks. Breeding occurred throughout the year, with an increased incidence during the wet season. Juveniles entered the populations over an extended period, and recruitment was low. Resident animals tended to utilize discrete 'core-areas', and showed a clear preference for Dense Forest domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…There is some evidence that Melomys burtoni in the Northern Territory may use rainforest as refugia in the dry season and disperse more widely after rain (Kerle & Burgman, 1984), although not all populations show such movement (Begg et al, 1983). We have no evidence that Melomys sp.…”
Section: Discussionmentioning
confidence: 66%
“…There is some evidence that Melomys burtoni in the Northern Territory may use rainforest as refugia in the dry season and disperse more widely after rain (Kerle & Burgman, 1984), although not all populations show such movement (Begg et al, 1983). We have no evidence that Melomys sp.…”
Section: Discussionmentioning
confidence: 66%
“…Melomys were monitored at seven independent 1‐ha (100 × 100 m) plots (sites 1–7) spread out across Indian Island using a standard mark–recapture trapping regime designed for a monitoring project (Begg et al 1983, Kemper et al 1987). Sites in the north (quoll‐invaded) and south (quoll‐free) of the island were between 8.7 and 9.8 km apart (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of this species on the north Australian mainland have demonstrated a similar strong predilection for these habitats (Begg et al, 1983;Kerle & Burgman, 1984).…”
Section: (3)mentioning
confidence: 97%